2015
DOI: 10.1093/nar/gkv1374
|View full text |Cite
|
Sign up to set email alerts
|

Structural requirements for protein-catalyzed annealing of U4 and U6 RNAs during di-snRNP assembly

Abstract: Base-pairing of U4 and U6 snRNAs during di-snRNP assembly requires large-scale remodeling of RNA structure that is chaperoned by the U6 snRNP protein Prp24. We investigated the mechanism of U4/U6 annealing in vitro using an assay that enables visualization of ribonucleoprotein complexes and faithfully recapitulates known in vivo determinants for the process. We find that annealing, but not U6 RNA binding, is highly dependent on the electropositive character of a 20 Å-wide groove on the surface of Prp24. During… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 46 publications
1
51
0
Order By: Relevance
“…1A). Indeed, telestem mutations that are expected to destabilize the ISL and induce an alternative U6 structure give rise to enhanced spontaneous U4/U6 annealing (36), and destabilization of the telestem in the human system promotes U4/U6 formation (37). Telestem formation is prevented in yeast U4/U6 (38), presumably by the coaxially stacked U4/U6 stems I and II intervening between its branches (22,31,39).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1A). Indeed, telestem mutations that are expected to destabilize the ISL and induce an alternative U6 structure give rise to enhanced spontaneous U4/U6 annealing (36), and destabilization of the telestem in the human system promotes U4/U6 formation (37). Telestem formation is prevented in yeast U4/U6 (38), presumably by the coaxially stacked U4/U6 stems I and II intervening between its branches (22,31,39).…”
Section: Discussionmentioning
confidence: 99%
“…Prp24 may have a second function in disrupting U6/U2 interactions after splicing (48,49). During U4/U6 annealing, three RNA recognition motifs of Prp24 interlock with the U6 ISL, asymmetrical bulge, and telestem (48), giving rise to an electropositive groove, which could mediate U4/U6 stem I annealing (36,48). Subsequent formation of U4/U6 stem II might then lead to displacement of Prp24 and complete U4/U6 assembly (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The four RNA recognition motif (RRM) domains of Prp24 wrap around spliceosomal U6 snRNA, making extensive contacts with double and single-stranded regions of the RNA (105). Reorientation of these domains is presumably needed to allow remodeling of U6 base pairs (106). Yeast La protein binds the 3′ ends of pol III transcripts (107, 108) and chaperones misfolded pre-tRNAs (109) and other small nuclear RNAs (110).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, the telestem may prove most important at other stages in splicing. It has recently been demonstrated that the telestem assists in U4/U6 annealing by the assembly factor Prp24 (14). Thus, while the U6 ISL is an essential component of spliceosomal catalysis, the U6 telestem likely functions in tri-snRNP assembly.…”
Section: Introductionmentioning
confidence: 99%